Occupational stress forces in security: A comparative study [Stresse ocupacional em forças de segurança: Um estudo comparativo] - Helena Gonçalo (2010)
This work analyzes occupational stress in two groups of security officers, one working in a public context (n=95) and the other one working in a prison context (n=237). We applied an evaluation protocol with measures of global stress, burnout, organizational commitment, satisfaction with life, professional satisfaction and desire to leave the profession. The fidelity and validity of the instruments were very acceptable. The results of burnout pointed out a remarkable frequency of emotional exhaustion (values between 12% and 26%) followed by cynicism (values between 8% and 21%) and low professional effectiveness (values between 8% and 21%) (only one participant showed burnout values in the three dimensions simultaneously). Comparative analysis between groups showed that correctional officers had more negative working experiences (e.g., higher levels of burnout and desire to leave the profession and lower levels of organizational commitment, satisfaction with life, and professional satisfaction). The possible factors that contribute to these results are discussed as well as the implications to future research.